Review on Smart Drip Irrigation and Fertigation using IOT & WSN - Sardeshmukh, M. M.; Warkhedkar, Vrushali (International Journal of Computer Sciences and Engineering, 2019)
In agriculture, despite large-scale funding with extension of irrigation services and it is a major concern that many sectors are facing deficits in management of water. Irrigation system is one of the major aspects to be enriched meeting the economic and sustainable challenges of the farmers. Recent trends in the area of Wireless Sensor Networks (WSN) have influenced a wide implementation of various applications in the area of precise agriculture. WSNs for environmental condition monitoring with defined knowledge are used for estimating crop growth and yield properties. The proposed system automates the irrigation and fertigation using WSN to make comparatively high yield than the traditional methods. Irrigation scheduling is estimated by use of WSNs real time monitoring of weather and soil properties. The exigent need for solving the constraints, Evapotranspiration (ET) system is integrated with irrigation module which uses Penman-Monteith FAO-56 model for calculating crop water need. The disadvantages of traditional agricultural systems remove by utilizing water resource efficiently. As a result, the proposed system helps in water conservation to a great extent and also reduces soil erosion as only the required fertilizers are injected via the drip system. The paper also includes the implementation and results of surface drip irrigation and sub-surface drip irrigation are implemented in maize and sugarcane field respectively.